2021
DOI: 10.3389/fmolb.2021.783301
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationship of the Disintegrin Family: Sequence Signature and Integrin Interaction

Abstract: Disintegrins are small cysteine-rich proteins found in a variety of snake venom. These proteins selectively modulate integrin function, heterodimeric receptors involved in cell-cell and cell-matrix interaction that are widely studied as therapeutic targets. Snake venom disintegrins emerged from the snake venom metalloproteinase and are classified according to the sequence size and number of disulfide bonds. Evolutive structure and function diversification of disintegrin family involves a stepwise decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 145 publications
1
22
0
Order By: Relevance
“…It is reported that CAT venoms have hydrophilic Dis with a molecular mass higher than 4 kDa. 36,43 Our results demonstrated an 8.9 kDa band (Fig. 3(D)), which could correspond to Dis.…”
Section: Partition Of Clarified Venomsmentioning
confidence: 53%
“…It is reported that CAT venoms have hydrophilic Dis with a molecular mass higher than 4 kDa. 36,43 Our results demonstrated an 8.9 kDa band (Fig. 3(D)), which could correspond to Dis.…”
Section: Partition Of Clarified Venomsmentioning
confidence: 53%
“…Then, obtained fractions were desalted using Amicon Ultra-0.5 ml and their ability to inhibit platelet aggregation or blood plasma clotting were estimated as it was described above. Fraction 4 eluted by 0.5 M NaCl possessed anti-aggregatory and anti-clotting activity that can be a consequence of action of protease specific to fibrinogen that was found in studied venom previously [5]. Such proteases cleave fibrinogen, which also inhibits the platelet aggregation that is strongly dependent on fibrinogen [18].…”
Section: Purification and Characterization Of Platelet Aggregation In...mentioning
confidence: 80%
“…Such polypeptides were mostly found in the venom of Viperidae and crotalidae families of snakes and later became a molecular platform for the development of anti-platelet drugs [4]. Mostly these polypeptides are disintegrins targeted to the glycoprotein IIb/IIIa (GPIIb/IIIa) receptor of platelets that are able to prevent interaction with fibrinogen and thus suppress platelet aggregation [5]. Also, the ability of snake venom disintegrins to block integrin functions allows the presumption of possible anti-cancer therapeutic potential, which…”
mentioning
confidence: 99%
“…To this end, conformational ensembles of the KTS-disintegrins (ligand) and the DIα1 as a receptor were used for the cross-docking. In the literature, the interaction between Obtustatin, Viperistatin, and Lebestatin with the domain αI of integrin α1β1 domains is based on experimental data suggesting that 21 KTS 23 are directly involved in the binding activity of these disintegrins [26]. However, in a previous investigation, it was hypothesized that the snake venom disintegrins interaction with α1β1 may not be limited to the KTS triplet, and that other key residues may be involved in the complex's formation.…”
Section: Discussionmentioning
confidence: 99%
“…The first step of the docking ensemble preparation involves two PDB entries of the DIα1 domain of α1β1 integrin (receptor) used to perform our computational study. The conformational ensemble for the receptor, was obtained using two structures of the DIα1 domain corresponding to PDB entries 1PT6 (X-ray crystallography structure) and 2M32 (NMR structure) representing the bound and the unbound state for a collagen mimetic peptide, respectively [26,37]. The selected structures of the receptors correspond to the lowest energies belonging to predefined local minimums [38].…”
Section: Docking Ensemble Preparationmentioning
confidence: 99%